Mediation In Indonesian And Wakai/Chotei In Japan: A Comparative Study - Kusano Yoshiro; Kawata Sozaburo (Yuridika, 2020)
Indonesian basic laws such as Civil Code and Code of Civil Procedure are those legislated in the Dutch colonial era and effective in written in Dutch language as genuine text as mentioned in other parts of this paper. Therefore you need amendment of laws to reform civil litigation system including reconciliation and mediation. Indonesians understand this point and they pointed out the issue of amendments of colonial laws at policy level and the do list up Code of Civil Procedure in the National Legislation Program in the parliament with draft written already. One issue of negotiation with the Supreme Court as one of Indonesian governmental body in relation with this project is about who to be sent to training in Japan. Training in a foreign country is a very attractive kind of technical cooperation. If the Japanese side paid much attention toward selection of trainees, then the training would be treated as a mere reward before retirement by the counter part. Those who we cannot expect a good performance or those who cannot make impact upon their bureaucracy might by chance participate the training.